2015
DOI: 10.3892/mmr.2015.4604
|View full text |Cite
|
Sign up to set email alerts
|

CK0403, a 9-aminoacridine, is a potent anti-cancer agent in human breast cancer cells

Abstract: Abstract. 3-({4-[4-(Acridin-9-ylamino)phenylthio]phenyl} (3-hydroxypropyl)amino)propan-1-ol (CK0403) is a sulfur-containing 9-anilinoacridine analogue of amsacrine and was found to be more potent than its analogue 2-({4-[4-(acridin-9-ylamino)phenylthio]phenyl}(2-hydroxyethyl)amino) ethan-1-ol (CK0402) and amsacrine in the inhibition of the topoisomerase II-catalyzed decatenation reaction. A previous study by our group reported that CK0402 was effective against numerous breast cancer cell lines, and the combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…To the best of our knowledge, the present study demonstrated for the first time the effect of Girdin silencing on different subtypes of breast cancer. Breast cancer has one of the highest incidences in females worldwide, and it is the primary cause of mortality in female patients with cancer (1). Breast cancer has long been a leading cause of mortality in women of both developed and developing countries (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the present study demonstrated for the first time the effect of Girdin silencing on different subtypes of breast cancer. Breast cancer has one of the highest incidences in females worldwide, and it is the primary cause of mortality in female patients with cancer (1). Breast cancer has long been a leading cause of mortality in women of both developed and developing countries (13).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer has one of the highest incidences in females worldwide, and it is the primary cause of mortality in female patients with cancer (1). At present, various breast cancer treatment methods have limitations, for example; surgery does not preclude hematopoietic or lymphatic dissemination leading to distant metastasis (2).…”
Section: Introductionmentioning
confidence: 99%
“…A summary of the most efficient 9-aminoacridines on cancer cell lines is given in Table 1. F I G U R E 2 7 Structure of sulfur-containing 9-amino-acridine derivatives 35a-b (Sun et al, 2016) F I G U R E 2 8 Structure of 9-phenoxyacridine derivative 36 (Bacherikov, 2014) 7 | CONCLUSION 9-Substituted acridines have been the focus of study since the early 20th century, and the need to develop novel derivatives with anticancer, antibacterial, antimalarial, or other biological activities is still as strong as ever. Together with other tricyclic aromatic heterocycles, 9-substituted acridines remain among the most intensely studied agents in this field.…”
Section: Anticancer Activity Of Other 9-substituted Acridine Derivamentioning
confidence: 99%
“…Sun, Chen, Kwon, and Chen (2016) investigated two new sulfur‐containing 9‐anilinoacridine analogs of amsacrine 35a–b (Figure 27) against various breast cancer cell lines (MCF‐7, MDA‐MB‐231, BT474, and SKBR‐3) and the noncancerous MCF‐10A cell line using a sulforhodamine B assay. The results showed that derivative 35a displayed a more potent level of growth inhibition than derivative 35b in all of the breast cancer cell lines with the exception of MCF‐7.…”
Section: Anticancer Efficacy Of 9‐aminoacridine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation